Pengaturan Sanksi Pidana Terhadap Penyelenggara Negara Yang Melaporkan Harta Kekayaan Secara Tidak Benar - Tuharea, Chindy Ameilia Putri; Ardianto, Syaifullah Yophie; Ferawati, Ferawati (Peneliti.net, 2024)
State Administrators' Wealth Report (LHKPN) is an obligation for State Administrators as an effort to prevent the occurrence of Corruption, Collusion and Nepotism (KKN) practices. However, there is a weakness in the regulation of sanctions in the regulations related to LHKPN because there are no criminal sanctions that can be imposed for reporting assets incorrectly. This causes the emergence of criminal acts, namely fraud and falsification in reporting. Therefore, criminal sanctions are needed to threaten State Administrators not to falsify their wealth reporting in the LHKPN. The aim of this research is first to describe the urgency of imposing criminal sanctions on State Administrators who report assets incorrectly. Second, formulate arrangements for criminal sanctions in the future for State Officials who report assets incorrectly The type of research used is normative legal research using library materials as data and reference sources. This research requires secondary data consisting of primary, secondary and tertiary legal materials. The data collection technique used by researchers is literature study. This research uses a qualitative analysis method by interpreting legal materials. In drawing conclusions, researchers use a deductive method, namely drawing conclusions from general statements or propositions to specific statements or propositions. From the results of the discussion and research carried out, it can be concluded that, Firstly, the urgency of imposing criminal sanctions on State Administrators who report assets incorrectly is because Law Number 28 of 1999 only regulates administrative sanctions for those who do not comply with reporting LHKPN, preventing the emergence of criminal acts in LHKPN , as well as creating fear and preventing State Administrators from reporting assets incorrectly. Second, the formula for regulating criminal sanctions against State Officials who report assets incorrectly in the future is criminal sanctions in the form of fines and additional criminal sanctions in the form of confiscation of assets that are not officially reported in the LHKPN.